Does energy policy hurt international competitiveness of firms? A comparative study for Germany, Switzerland and Austria - Spyros Arvanitis; Sandra Gottschalk; Michael Peneder; Christian Rammer; Tobias Stucki; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2016)
This paper investigates the impact of energy policies on the export performance of firms. There has been a long policy debate on potentially negative impacts of cost-increasing energy policies on international competitiveness. We use firm-level data from three countries with similar industry structure but different energy policies: Germany, Switzerland, and Austria. We rely on firm manager assessments on the relevance of energy policy (in terms of taxes, regulations, standards, subsidies and demand stimulation) for their firm operation and link data on the adoption and development of new energy technologies. Regression analyses and matching approaches both show very few impacts of energy policy on export performance, suggesting that either policy impacts on firms' cost are negligible in the period of study (2012 to 2014) or likely negative impacts are balanced by the adoption of new technology.
Keywords: O33; Q48; Q55; F14; F18; 330; Energy policy; technology adoption; competitiveness; export; matching approach